2023
DOI: 10.1001/jamaneurol.2023.1988
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Lesion-Related Epilepsy to a Human Brain Network

Abstract: ImportanceIt remains unclear why lesions in some locations cause epilepsy while others do not. Identifying the brain regions or networks associated with epilepsy by mapping these lesions could inform prognosis and guide interventions.ObjectiveTo assess whether lesion locations associated with epilepsy map to specific brain regions and networks.Design, Setting, and ParticipantsThis case-control study used lesion location and lesion network mapping to identify the brain regions and networks associated with epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 94 publications
1
6
2
Order By: Relevance
“… 6 Similar to these, authors found that after stroke, bigger lesions and higher cortical damage were associated with a higher epilepsy risk, while subcortical damage was associated with a reduced epilepsy risk. 5 Contrary to previous literature, authors found no difference in epilepsy risk based on vascular territory or lobar location. 5 They controlled all further analyses for these potential risk factors for post-stroke epilepsy.…”
Section: Commentarycontrasting
confidence: 69%
See 3 more Smart Citations
“… 6 Similar to these, authors found that after stroke, bigger lesions and higher cortical damage were associated with a higher epilepsy risk, while subcortical damage was associated with a reduced epilepsy risk. 5 Contrary to previous literature, authors found no difference in epilepsy risk based on vascular territory or lobar location. 5 They controlled all further analyses for these potential risk factors for post-stroke epilepsy.…”
Section: Commentarycontrasting
confidence: 69%
“…3 Over the past decade, the notion that epileptogenicity in both lesional and nonlesional focal epilepsies is distributed across an epileptic network has become more widely accepted. 4 In this case-control study, 5 Schaper et al build upon the existing understanding of epilepsy networks and attempt to answer an exciting question using advanced lesion location and lesion network mapping techniques: Does lesion-related epilepsy across various etiologies and locations map to specific brain networks? The authors compared patients with poststroke epilepsy in the discovery dataset to controls who had strokes but did not develop epilepsy.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to its role as a convergent point of the pallidothalamic tract from the globus pallidus interna (GPi) to the thalamus in the basal ganglia‐thalamocortical circuit (BTCC) 5 . Recent studies have highlighted the involvement of the basal ganglia in the pathogenesis of FBTCS, seizure termination, and the network of poststroke epilepsy 6–9 . This has led to a growing understanding of the potential therapeutic effects of Forel‐H‐tomy on epilepsy.…”
Section: Introductionmentioning
confidence: 99%